(untitled) (International Journal of Design (INJUDES), 2022)
This study aims to develop and analysis the design of a heat exchanger (HE) for water-based Mos2 nano-lubricant production using a simple one-pass HE shell and tube type. Specifications of the designed HE are shell length 4.8768 m, shell diameter 0.889 m, tube outer diameter 0.0254 m, and thickness 0.0217 m. The calculation is then performed manually using the Microsoft Excel application. The results showed that the shell and tube HE designs with a one-pass type have laminar flow with an effective value of 95.38 percent and an NTU value of 31.79. This HE designs has a high effectiveness so that it is considered effective for use. This result is very important to maximize the efficiency of shell and tube heat exchange. This HE designs analysis can then be used as a learning tool for the design process, operating mechanism, and HE performance analysis.